(untitled) (Global Journal of Science Frontier Research, 2012)
This study was carried out to investigate the levels of aflatoxins in some agricultural commodities sold at Baboko market in Ilorin. The agricultural commodities were grains, root and tuber products, onions, cray-fish and stock-fish. Aflatoxin B1 (AFB1) in grains ranged between 2.57±0.61 in wheat and 21.72±2.92 ppb in sorghum, while AFB2 ranged between 0.46±0.23 and 6.66±2.11 ppb in all the samples investigated. Varying levels of AFB2, AFG1 and AFG2 were detected in grain samples. AFB1concentrations in root and tuber were: 5.66±1.69 ppb in yam chips and 4.20±0.90 ppb in cassava chips, whereas AFB2 was observed to be 2.97±1.69 and 1.58±0.30 ppb respectively. AFG1 concentration in yam chips was 3.52±0.24 ppb while that of cassava chips was 4.80±0.31ppb. Cumulative higher levels of aflatoxins B were observed for onion samples when compared to aflatoxin G. It was generally observed that stock-fish had higher levels of aflatoxins when compared to cray-fish with exception of AFG2 in cray-fish which was higher than that of stock-fish.